Metabolic reprogramming of pulmonary fibrosis - Li, Jiaxin; Zhai, Xiaoxuan; Sun, Xiao; Cao, Shengchuan; Yuan, Qiuhuan; Wang, Jiali (Frontiers in Pharmacology, 2022)
Pulmonary fibrosis is a progressive and intractable lung disease with fibrotic features that affects alveoli elasticity, which leading to higher rates of hospitalization and mortality worldwide. Pulmonary fibrosis is initiated by repetitive localized micro-damages of the alveolar epithelium, which subsequently triggers aberrant epithelial-fibroblast communication and myofibroblasts production in the extracellular matrix, resulting in massive extracellular matrix accumulation and interstitial remodeling. The major cell types responsible for pulmonary fibrosis are myofibroblasts, alveolar epithelial cells, macrophages, and endothelial cells. Recent studies have demonstrated that metabolic reprogramming or dysregulation of these cells exerts their profibrotic role via affecting pathological mechanisms such as autophagy, apoptosis, aging, and inflammatory responses, which ultimately contributes to the development of pulmonary fibrosis. This review summarizes recent findings on metabolic reprogramming that occur in the aforementioned cells during pulmonary fibrosis, especially those associated with glucose, lipid, and amino acid metabolism, with the aim of identifying novel treatment targets for pulmonary fibrosis.